Analysis and Comparison of Financial Technology Peer to Peer Lending Sharia and Conventional - Alfi Amalia; Andri Soemitra (Journal of Education, Humaniora and Social Sciences (JEHSS), 2022)
Among the types of fintech that are growing rapidly in Indonesia at this time are peer-to-peer lending fintechs, technology-based money-borrowing fintechs through peer-to-peer lending services have advantages, namely simple requirements and a fast process compared to borrowing and borrowing. money to banking institutions. In addition to conventional peer to peer lending fintech services, there are also sharia peer to peer lending fintech services. This study aims to identify and analyze the differences between conventional peer to peer lending fintech and sharia peer to peer lending fintech and how to apply sharia principles in sharia peer to peer lending fintech. So that it can guarantee the Indonesian people, whose residents are generally Muslim, will the halal products offered. The differences between sharia peer to peer lending fintech and conventional peer to peer lending fintech include: First, from the regulatory aspect that governs it, Second, the existence of a Sharia Supervisory Board in sharia fintech, Third, in the working mechanism between conventional fintech and sharia fintech which makes the difference of course with the existence of sharia principles. And fourth, in practice, in sharia fintech generally the loans provided are productive and more varied. Meanwhile, in its application, sharia peer to peer lending fintech is in accordance with the Fatwa of the MUI National Sharia Council No. 117/DSN-MUI/II/2018. in the working mechanism between conventional fintech and sharia fintech, the difference is of course with the existence of sharia principles. And fourth, in practice, in sharia fintech generally the loans provided are productive and more varied. Meanwhile, in its application, sharia peer to peer lending fintech is in accordance with the Fatwa of the MUI National Sharia Council No. 117/DSN-MUI/II/2018. in the working mechanism between conventional fintech and sharia fintech, the difference is of course with the existence of sharia principles. And fourth, in practice, in sharia fintech generally the loans provided are productive and more varied. Meanwhile, in its application, sharia peer to peer lending fintech is in accordance with the Fatwa of the MUI National Sharia Council No. 117/DSN-MUI/II/2018.